(untitled) (European Journal of Pure and Applied Mathematics, 2024)
A study of θ-open sets in generalized topological spaces started in 2011 by Min wkm. In this paper, we introduce the concepts of sθ-open sets, sθ-closed sets, sθ-continuous functions and sθ-irresolute functions on generalized topological spaces. We also study some basic properties of such sets and functions.